ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS AUDIT APARAT INSPEKTORAT KOTA/KABUPATEN DI JAWA TENGAH - Precilia Prima Queena; Abdul Rohman (Diponegoro Journal of Accounting, 2012)
The objectives of this research to empirically analyze the influence of independency, objectivity, knowledge, job experience, integrity, ethics, and auditor’s proffesional skepticism of audit quality. The population in this research are all auditor’s who worked on the Inspectorate of the city/ county in Semarang, Ungaran, Salatiga, Kendal, and Pekalongan. Sampling was conducted using a purposive sampling method and number of samples of 62 respondents. Primary data collection method used is questionnaire method. The data analysis technique used in This research is the technique of multiple regression analysis. The result showed that the objectivity, knowledge, integrity, ethics, auditor’s proffesional skepticism have a positive and significant impact on audit quality, while the independence and job experience of the variables do not have a significant impact on audit quality. Value of the coefficient of determination indicates that together the independency, objectivity, knowledge, experience, integrity, ethics, and auditor’s proffesional skepticism contribute to dependent variable (quality audit) of 82,8% while the remaining 17,2% are influenced by other outside factor model.